Mycoplasma synoviae and Reovirus: (re)emerging infectious diseases in broiler Breeders - MOREIRA, F. A.; CARDOSO, L.; COELHO, A. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Broiler breeders are one of the most important components of the poultry industry. This type of birds is susceptible to several agents that interfere with the immune system and predispose to infection. If transmission of pathogens to progeny is considered, their economic impact will be amplified in the broiler farms, compromising the entire production results. Construction of multi-age farms poses a significant epidemiological risk. In fact, these farms have grown in size and density, and an ideal environment has been created for agents such as Mycoplasma synoviae and Reovirus to thrive. A general review of the scientific literature concerning M. synoviae and Reovirus in broiler breeders is presented on their epidemiology, economic importance, pathogenesis, lesions, clinical signs, diagnosis, control, treatment and prevention.